New nonlinear algorithms for narrowband interference suppression in CDMA spread-spectrum systems. - Kun-Jie Wang (IEEE Journal on selected areas in communications)
The narrow-band interference suppression capability of spread-spectrum systems can be further enhanced by employing interference suppression filters. This paper proposes a number of new nonlinear algorithms for narrow-band interference suppression in code division multiple access spread-spectrum systems. Our research consists of two parts. (1) We propose a multiuser decision-directed Kalman (MDK) filter, which has the same performance as the nonlinear approximate conditional mean (ACM) filter but a much simpler algorithm. (2) We use the nonlinear function in the ACM and the MDK filters to develop nonlinear adaptive least mean square filters with significantly improved performance. Simulation results indicate that our nonlinear algorithms outperform conventional linear ones